Chemical Composition and Anticancer Activity of Essential Oils from Cyperaceae Species: A Comprehensive Review - José Jailson Lima Bezerra; Anderson Angel Vieira Pinheiro; Antônio Fernando Morais de Oliveira (Scientia Pharmaceutica)
Cancer is one of the leading causes of mortality worldwide, and the currently available therapies are often associated with severe side effects, including nephrotoxicity, hepatotoxicity, and cardiotoxicity. In this context, essential oils (EOs) have stood out as a less toxic natural alternative, with their anticancer potential widely investigated in in vitro and in vivo studies. The present study aimed to review, for the first time, the chemical composition, anticancer potential, and biological safety of EOs extracted from species of the Cyperaceae family. Research was conducted in different databases, covering publications from the first report on the topic in 1989 to November 2024. This review highlights 33 Cyperaceae species known to produce essential oils, with sesquiterpenes (67%) identified as the predominant compounds. The notable compounds across multiple species include cyperene, cyperotundone, caryophyllene oxide, and mustakone. Regarding the pharmacological potential, the EOs of Cyperus rotundus, Cyperus kyllingia, and Cyperus longus exhibited high cytotoxic activity against the HCT-116, HepG2, MCF-7, HeLa, and NCI-H187 cell lines. The mechanisms of action associated with the anticancer effect of EOs include DNA fragmentation, cell cycle arrest, and induction of apoptosis. Acute toxicity reports indicate that only the EOs of Cyperus articulatus have been evaluated in rodents and deemed biologically safe.